Identity, opportunity and hope :an Aboriginal model for alcohol (and other drug) harm prevention and intervention - Nichols, Fiona Troup (Curtin University, 2002)
The fieldwork for this study was conducted in the West Kimberley region of Western Australia between 1997 and 1999. Qualitative and quantitative information provided by 170 Aboriginal participants enabled an exploration of the context and patterns of Aboriginal alcohol use; Aboriginal perceptions of the alcohol issue, existing interventions, research findings, 'culture' and its role in prevention and intervention; and participants' incorporation of these perceptions into an Aboriginal model for alcohol misuse prevention, intervention and evaluation. Findings were based on the results of individual and focus group interviews, serial model-planning focus groups, documentary data and observation.Study findings generally suggest that in addition to self-determination and support components, 'cultural context' retains an important role for many remote area Aboriginal people. The findings from a small sub-sample tentatively suggest that 'cultural' disruption, in addition to the socio-economic consequences of colonisation and dispossession, may play an important role in alcohol misuse. Consequently, it appears that in combination with self-determination and support components, the strengthening of a locally-defined 'cultural' context may have an important role in alcohol misuse prevention and intervention - an approach frequently unrepresented in existing symptom-focused models and one inviting further investigation. The model developed by study participants expands significantly on existing symptom-focused approaches through a comprehensive life-enhancement focus on aspects of identity, opportunity and hope. This approach adds depth and meaning to understandings of cultural appropriateness and of culturally relevant models for substance misuse prevention and intervention.